2011
DOI: 10.1007/s11684-011-0109-y
|View full text |Cite
|
Sign up to set email alerts
|

The influence of brain death on donor liver and the potential mechanisms of protective intervention

Abstract: Brain-dead donors have become one of the main sources of organs for transplantation in Western countries. The quality of donor organs is closely related to the outcome of the transplantation. Experimental studies have confirmed the inferior graft survival of livers from brain-dead donors compared with those from living donors. Studies conducted in the past 10 years have shown that brain death is associated with effects on the decreased donor organ quality. However, whether the decrease in the viability of dono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…[70][71][72] It is quite possible that the SCI initiates a similar ''neurogenic disease'' state in peripheral organs and contributes to the overall poor health and reduced longevity in the SCI population. The peripheral liver dysfunction in turn could potentially contribute to spinal cord dysfunction because hepatic myelopathy has been described in patients presenting with progressive spasticity and paresis.…”
Section: Sauerbeck Et Almentioning
confidence: 99%
“…[70][71][72] It is quite possible that the SCI initiates a similar ''neurogenic disease'' state in peripheral organs and contributes to the overall poor health and reduced longevity in the SCI population. The peripheral liver dysfunction in turn could potentially contribute to spinal cord dysfunction because hepatic myelopathy has been described in patients presenting with progressive spasticity and paresis.…”
Section: Sauerbeck Et Almentioning
confidence: 99%
“…High levels of catecholamines can also lead to overload of intracellular calcium, depletion of adenosine triphosphate, and therefore overproduction of oxygen free radicals and cell injury. Thereafter, a hypotensive phase commences, due to gradual depletion of catecholamines, causing further reduction of the oxygen supply to the internal organs [4,5]. Therefore, it is generally believed that organs should be procured as soon as possible once brain death is confirmed.…”
Section: Introductionmentioning
confidence: 99%
“…Comparison of the outcomes between organs from living‐related donors and organs from brain dead donors has indicated that brain death has detrimental effects on allograft function . Importantly, most organs are harvested from brain dead donors, and for certain organs, such as cardiac transplants, this is the sole source of donors.…”
Section: Introductionmentioning
confidence: 99%